Drug survival in the treatment of generalized pustular psoriasis: A retrospective multicenter study. Issue 2 (15th February 2021) - Kromer, Christian; Loewe, Emilia; Schaarschmidt, Marthe‐Lisa; Pinter, Andreas; Gerdes, Sascha; Herr, Raphael; Poortinga, Sietske; Moessner, Rotraut; Wilsmann‐Theis, Dagmar
Abstract: Generalized pustular psoriasis (GPP) is a rare, potentially life‐threatening inflammatory skin disease. Our aim was to assess patient and disease characteristics and analyze drug survival rates in the treatment of GPP in a real‐life setting. In this retrospective study, 201 treatment series of 86 patients with GPP treated at five University Medical Centers were analyzed. Overall, excellent response was reached in 41.3% of all treatment courses, partial response in 31.4%, and nonresponse in 27.3%. Biological treatment was significantly more effective than non‐biological therapies (excellent response: 47.4% vs 35.9%; P = .02). Overall, the median drug survival was 14.0 months (biologicals: 36.0 months vs nonbiologicals: 6.0 months; P < .001). The crude probability of survival was highest for secukinumab (hazard ratio [HR] of drug discontinuation compared with acitretin: 0.22), followed by ixekizumab and ustekinumab (HR: 0.38 each), adalimumab (HR: 0.59), etanercept (HR: 0.62), infliximab (HR: 0.69), cyclosporine (HR: 1.00), acitretin (reference for HR), fumaric acid esters (HR: 1.06), methotrexate (HR: 1.26), and apremilast (HR: 3.44); no drug discontinuation with guselkumab. Our results reveal high efficacy and drug survival, particularly for IL‐17 and IL‐(12)/23 antagonists. Thus, these biologics may be considered early in the therapeutic algorithm of GPP.